2022
DOI: 10.22438/jeb/43/5/mrn-4042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals in fish reproduction: A review

Abstract: Heavy metals are ubiquitous and deleterious contaminant present in the aquatic ecosystem. Their concentration has increased magnificently due to anthropogenic wastes, geochemical composition, farming and mining activities. Fishes are susceptible to heavy metal contamination and fishes live in aquatic environment which made them inevitable exposure to heavy metal. The excess release of contaminants into aquatic ecosystem has forced the fish to accumulate more heavy metal in their tissues. However, fishes reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…A study on their growth rate, survival rate, locomotor activity, and sensory activities indicated that zebrafish embryos exposed to Cd exhibited delayed hatching and a higher mortality rate [102]. Another toxicity assessment analysis of zebrafish showed abnormalities in embryonic development, producing offspring with varying extents of deformity (Table 1) [18,105,108]. Embryonic abnormalities account for impairments in the olfactory placode and defects in the head where the subdivisions of the brain are not well defined, therefore ultimately targeting neurogenesis [109,110].…”
Section: Developmental Effects Of Cadmium On Freshwater Fishmentioning
confidence: 99%
“…A study on their growth rate, survival rate, locomotor activity, and sensory activities indicated that zebrafish embryos exposed to Cd exhibited delayed hatching and a higher mortality rate [102]. Another toxicity assessment analysis of zebrafish showed abnormalities in embryonic development, producing offspring with varying extents of deformity (Table 1) [18,105,108]. Embryonic abnormalities account for impairments in the olfactory placode and defects in the head where the subdivisions of the brain are not well defined, therefore ultimately targeting neurogenesis [109,110].…”
Section: Developmental Effects Of Cadmium On Freshwater Fishmentioning
confidence: 99%
“…Moreover, metals can induce morphological changes in tissues, such as gill damage and liver abnormalities, while also interfering with cellular functions, including enzyme activity and gene expression [22]. Several other studies have indicated that fish exposed to metals experience a decline in various reproductive parameters, including the gonadosomatic index (GSI), fecundity, hatching rate, fertilization success, abnormal shape of reproductive organs, and ultimately reproductive failure [23][24][25]. Moreover, various fish species can serve as effective biological indicators for assessing the extent of exposure to metals and other pollutants [15,16].…”
Section: Effect Of Metals On Fish Due To Exposurementioning
confidence: 99%
“…In the soil, mercury has a long retention time; once accumulated, it continues to be released into surface waters and other environments for prolonged periods [2]. The contamination of the aquatic environment with heavy Fishes 2023, 8, 445 2 of 13 metals threatens the recruitment and survival of aquatic fauna due to detrimental effects on metabolism, growth, and reproduction [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%